Pengaruh Kompensasi, Budaya Organisasi Dan Komitmen Organisasi Terhadap Kinerja Karyawan (Studi Pada PT. Marinal Indoprima Sumenep-Madura) - Jayak Ferdwiyono; Abd Kodir Djaelani; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2020)
AbstractEvery organization will always improve the quality of its resources so that its performance is satisfactory. Employees who have commitment and culture towards the organization have the potential to improve performance. In addition, compensation is also one of the drivers for improving employee performance. This study aims to determine the effect of compensation, organizational culture and organizational commitment to the performance of the employees of PT Marinal Indoprima.This type of research is quantitative research by distributing questionnaires. The sample used in this study amounted to 52 out of 599 populations. The results showed that partially compensation had a significant effect on employee performance. Organizational culture influences employee performance. Organizational commitment influences employee performance. While simultaneously showing compensation, organizational culture and organizational commitment significantly influence Employee Performance. Keywords: Compensation, Organizational Culture, Organizational Commitment, Employee Performance